Effective factors on nurses’ job satisfaction - elnaz asghari; tahereh khaleghduost; fariba asgari; ehsan khazemnezhad (Journal of Holistic Nursing and Midwifery)
Introduction: Job satisfaction is a positive feeling and attitude towards one's job. Identification of effective factors on job satisfaction is important because it plays vital role on organizational outcome and even on ones' personal life.